Exploring the Connection between Physical and Mental Health in Women and Dog Ownership - Yuni Astuti; Bekir Erhan Orhan; Hendra Setyawan; Aydin Karacam; Nugroho Susanto (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2024)
The connection between pet ownership and human well-being, especially the role of dogs, has been an area of increased focus for researchers. This qualitative study investigates the intricate relationship between physical and mental health in women who have dogs. Through semi-structured interviews with 20 women and open-ended questions designed specifically for the topic, this study provided a platform for participants to share their experiences and thoughts, leading to a deeper understanding of the issue. The research strongly indicates that having a dog has a beneficial effect on mental health. Participants reported feeling less stress and anxiety, an uplift in spirits, and increased motivation. They also noted enhanced social bonds and emotional support from their canine companions. Conversely, the study also calls attention to specific challenges linked with dog ownership. The financial burden, time investment, and care responsibilities could increase stress for some. Health conditions or allergies could intensify discomfort for dog owners, and the emotional impact of a pet's illness or loss could lead to profound grief. The study underscores the importance of acknowledging individual factors that influence the impact of dog ownership on mental health. By recognizing the benefits and the challenges of having a dog, individuals can make more informed choices about pet ownership and better prepare for any associated difficulties. Further research is necessary to deepen our understanding of the dynamics between human and canine well-being and devise strategies to enhance the mental health benefits for dogs and their owners. Supporting the human-canine relationship could significantly improve mental well-being and overall quality of life.